A knowledge base to assist a heuristic search approach to facility layout - Sirinaovakul, B.; Thajchayapong, P. (My University, 1994)
This paper presents a construction model for facility layout. An artificial intelligence technique has been used to solve the problems of allocating patterns within a layout. The designed system consists of pattern allocation, a heuristic search and a knowledge base system. The system first generates alternative layouts by using a pattern allocation. The heuristic search searches for the best layout from these generated alternatives. The heuristic function, or closeness weight, is also used for directing the search process to the most profitable choice of layout by acquiring knowledge from the knowledge base. An experimental system is constructed for testing purposes only. The results from the system show potential for solving complex facility layout problems. © 1994 Taylor & Francis Group, LLC.